'Low carbon city development' (LCCD) as a strategy for sustainable cities: The case of Rio de Janeiro, Brazil. (1st September 2013) - Rescalvo, Miguel; Lasa, Maite; D'Silva, Natasha; Barrios, Ramiro; Sommaripa, Leo; Scholz, Sebastian; Sugar, Lorraine
This article discusses how cities can contribute to climate change mitigation through an integrated approach involving low carbon development (LCD) as part of a city's strategic planning. Cities have an opportunity to link climate change policies to local developmental priorities. They can engage in sustainable development and take leadership in climate change initiatives by considering a LCD approach in which municipalities take advantage of integrated planning that ensures that emissions reductions strategies and socio-economic growth are not mutually exclusive. This article features the Low Carbon City Development (LCCD) Programme developed by the World Bank and DNV KEMA Energy and Sustainability as a framework for the integration of LCD and climate change mitigation actions with respect to implementation of strategic urban planning in cities.